HOLONOMY AND IT RALATION WITH THE FOLLATIONS - Sulca Paredes, Teodoro (2003)
We consider non-linear holomorphic vector fields Z defined in an open U of C2 wíth isolated singularity at the origin. We study a system of differential equations associated to the vector field Z, for the case in which the linear part of this field ís in Siegel' s domain. The concept of holonomy is used.